Joint and tandem source-channel coding with delay constraints - Jongtae Lim; Neuhoff, D.L. (2001 IEEE International Conference on Acoustics, Speech, and Signal Processing. Proceedings (Cat. No.01CH37221), 2001)
Two common source-channel coding strategies, joint and tandem, are compared on the basis of distortion vs. delay by analyzing specific representatives of each when transmitting analog data samples across a binary symmetric channel. Channel-optimized transform coding is the joint source-channel coding strategy; transform coding with Reed-Solomon coding is the tandem strategy. For each strategy, formulas for the mean-squared error and delay are found and used to minimize distortion subject to a delay constraint, for data modeled as Gauss-Markov. The results of such optimizations suggest there is a threshold such that when the permissible delay is above this threshold, tandem coding is better, and when below the threshold, channel-optimized transform coding is better.